Peningkatan Kompetensi Guru dalam Memberikan Feedback dan Mengelola Proyek Siswa dengan MagicSchool.AI - Tijan, Tijan; Abdilah, Yan Amal; Bashori, Muzakki; Suhardiyanto, Andi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve the competence of Pancasila and Citizenship Education teachers in providing learning feedback and managing student project assignments using MagicSchool.AI. This activity was motivated by challenges faced by teachers, namely, limited time to provide in-depth feedback to students and difficulties in effectively monitoring the progress of project assignments. Unlike an AI Chatbot, MagicSchool.AI is a Learning Management System focused on supporting learning activities, making it more suitable for teachers. The methods employed include counselling, participatory training, structured practice, and collaborative mentoring between lecturers, teachers, and students. Out of 80 teachers who joined the program, 24 completed the evaluation questionnaire. The evaluation results showed an overall average of 4.04 (high category). The highest score was in the teacher's ability to design and manage project/essay assignments with support from the MagicSchool.AI website, with an average of 4.25, while the lowest score was in understanding the basic concepts of engineering prompts, with an average of 3.79. In addition, the teacher's ability to provide feedback to students received an average of 4.17 for adjusting the content of automatic feedback to the rubric, 4.13 for monitoring the progress of student assignments, and 4.04 for providing feedback to students. These results highlight the potential of AI training as a strategic innovation to address time constraints, improve work efficiency, and strengthen the quality of project-based learning. Therefore, this program not only expands teachers’ digital literacy but also offers a replicable community service model to support educational transformation in the AI era.